A metal–polyphenolic nanosystem with NIR-II fluorescence-guided combined photothermal therapy and radiotherapy. Issue 87 (15th October 2021) - Li, Jie; Li, Wenxi; Xie, Lisi; Sang, Wei; Wang, Guohao; Zhang, Zhan; Li, Bei; Tian, Hao; Yan, Jie; Tian, Ye; Li, Zhenhua; Fan, Quli; et al.
Abstract : A polyphenolic semiconducting polymer was prepared to chelate the high- Z Hf ions, followed by coating of the amphiphilic polymers to form a nanostructure (CPPDA–Hf@Poloxamer nanoparticles) for precise lesion imaging and photothermal therapy. Abstract : Photothermal therapy (PTT) achieves substantive therapeutic progress in certain tumor types without exogenous agents but is hampered by the over-activated inflammatory response or tumor recurrence in some cases. Herein, we technically developed the metal–polyphenolic nanosystem with precise NIR-II fluorescence-imaging guidance for combining hafnium (Hf)-sensitized radiotherapy with PTT to regress tumor growth.